Factors affecting metformin plasma concentrations - Alawadhi, Sohaila (Curtin University, 2010)
Background: According to the United Kingdom prospective diabetes study, metformin is considered the drug of choice in overweight newly diagnosed type 2 diabetic patients. Metformin is well characterized as a substrate of the organic cation transporter (OCT) 1 and OCT 2. In vitro and in vivo studies have revealed that OCT1 and OCT2 genes exhibited polymorphic variations in different ethnic groups, and metformin uptake was impaired in individuals who carried polymorphic single nucleotide polymorphisms (SNPs). It was observed that in clinical practice there was inter-individual variation to metformin therapy; it could be due to a variety of reasons including genetic variations of the OCT1 and OCT2 genes. To date no genetic studies have been conducted on Arab populations to investigate the clinical effects of genetic polymorphisms of OCT1 and OCT2 genes on metformin plasma concentrations in diabetic populations.Objective: To investigate factors affecting metformin plasma concentrations and to analyse genetic variations of OCT1, OCT2, and serine threonine kinase (LKB1) genes in the United Arab Emirates (UAE) population. Also, to investigate the possible effects of genetic variations of these genes on metformin plasma concentrations among a diabetic group of patients in the UAE population.Study design: A cross sectional prospective study recruited control non-diabetic and diabetic (test) individuals from four different hospitals and health centres in the UAE. Diabetic patients had been prescribed metformin therapy for at least seven days. One fasting blood sample was taken to investigate metformin plasma concentrations, fasting plasma glucose, glycated haemoglobin, serum creatinine, and DNA genotypes.Results: Overall, 170 control non-diabetic and 292 diabetic subjects completed the study. The mean age for the diabetic patients was 54± 0.7 years, mean glomerular filtration rate (GFR) was 88 ±1.6 mL/min/1.73m2 , mean metformin dose was 1622 ±28 mg/day, and the mean metformin plasma concentration was 0.62 ±0.03 mg/L. Among the reported OCT1 SNPs in the database 12 were polymorphic in the UAE population, while five polymorphisms were reported in the OCT2 gene, and two were polymorphic in the LKB1 gene. One novel synonymous Ser 279 (A/G) SNP was found in exon 1 in the OCT2 gene that has not been reported in any other population with minor allele frequency (MAF) of 1.03%.The result of the current study showed that among the investigated variables, metformin dose, GFR, OCT1-E1 synonymous SNP rs1867351 and OCT1-E9 non-synonymous 488Arg>Met SNP were found to be associated with metformin plasma concentrations with p = 0.002, p = 0.008, p = 0.005, and p = 0.007 respectively.Conclusion: This is the first large study to investigate the allele frequencies of OCT1, OCT2, and LKB1 genes in the Eastern Mediterranean population, and to report the effect of genetic variations of drug transporters on metformin plasma concentrations. These findings emphasise that each ethnic group carries a unique genetic background that should be genotyped and investigated independently. It also highlights the important role played by the synonymous SNPs on the drug transporters function. In order to implement these findings in clinical practice, further pharmacoeconomic studies are recommended to evaluate the cost effectiveness of genotyping selected sub-groups of patients for genetic variations in OCT genes. It is also recommended that further pharmacogenomic studies should be carried out to investigate the impact of genetic variations in other candidate genes that might affect metformin efficacy and disposition, such as plasma membrane monoamine transporter (PMAT) and multidrug and toxic extrusion (MATE) genes.